Fractal Approach: Quantification of Seismicity in South Central Tibet - Paudyal, Harihar; Roy, PNS (BIBECHANA, 2012)
The South Central Tibet (SCT) region is inferred to be an extensional regime since it is predominantly associated with normal faulting with E-W oriented horizontal tension axis representing extension in eastwest direction. In this paper the fractal analysis is carried out using the seismicity data (mb≥3.5) for last 47 years (1963-2009) in SCT to the north of Central Himalaya. The entire study area is bounded by 29o-31o N and 85o-90o E. The study escorted to the recognition of a clustering events in two consecutive fifty events window having low spatial fractal correlation dimension (Dc) value ranging from 0.3638 to 0.5451 during the period between 07.26.1998 to 03.23.2002. Relatively two lower Dc obtained prior to strong event. Spatial-temporal clustering of events during low Dc period actually specifies a highly stressed region, leading to increase of shear strain causing weak zone from where the rupture propagation may ultimately nucleate causing large earthquake. This type of clustering pattern study using the well constrained catalogue data for the SCT region, which has a record of high seismic activity for the entire last two decades, can assist to enhance the understanding and mitigation of earthquake hazard. Keywords: Fractal spatial; correlation dimension (Dc); clustering; seismicity DOI: http://dx.doi.org/10.3126/bibechana.v8i0.5699 BIBECHANA 8 (2012) 116-126